2015
DOI: 10.1039/c5ob00898k
|View full text |Cite
|
Sign up to set email alerts
|

Achiral, acyclic nucleic acids: synthesis and biophysical studies of a possible prebiotic polymer

Abstract: The search for prebiotic, nucleic acid precursors is, at its best, a speculative undertaking. Given the complex structure of RNA, it is not very likely that RNA was the first information system in the universe and thus finding possible precursor/s i.e. pre-RNA remains an open challenge. We, in this paper, have tried to construct nucleic acid polymers with a simple acyclic, achiral backbone. Such a linear, achiral backbone may have been formed from simple monomers that may have existed in the "prebiotic soup". … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 73 publications
0
12
0
Order By: Relevance
“…Notably, TIPP (a pyrophosphatase) was included in all reaction mixtures before adding the primer template. We previously observed that adding TIPP prevented pyrophosphate (PP i )‐induced template and/or primer degradation (pyrophosphorolysis) . This process could even occur with 3′→5′ exonuclease‐deficient DNA polymerases to generate new deoxynucleotide triphosphates (dNTPs), which would lead to incorrect incorporation of monophosphates (MPs) .…”
Section: Resultsmentioning
confidence: 99%
“…Notably, TIPP (a pyrophosphatase) was included in all reaction mixtures before adding the primer template. We previously observed that adding TIPP prevented pyrophosphate (PP i )‐induced template and/or primer degradation (pyrophosphorolysis) . This process could even occur with 3′→5′ exonuclease‐deficient DNA polymerases to generate new deoxynucleotide triphosphates (dNTPs), which would lead to incorrect incorporation of monophosphates (MPs) .…”
Section: Resultsmentioning
confidence: 99%
“…Srivastava et al. designed achiral XNAs as candidates for the prebiotic genetic carrier in pre‐RNA world [24] . Diethanol amide nucleic acid (DEANA) has an achiral scaffold of eight main chain atoms, which is two atoms longer than natural systems (Figure 3).…”
Section: Negatively Charged Acyclic Xna Oligomersmentioning
confidence: 99%
“…Triethanol amino nucleic acid (TEANA) has also been synthesized (Figure 3). TEANA has an ethyl group as an internal linker between nucleobase and nitrogen in the backbone [24] . TEANA oligomers have not yet been evaluated.…”
Section: Negatively Charged Acyclic Xna Oligomersmentioning
confidence: 99%
“…The synthesis of N-alkylated A followed previously reported synthetic procedures. [16,33,40] Briefly, A was treated with potassium carbonate (K 2 CO 3 ) in anhydrous N,N-dimethylformamide (DMF), followed by the addition of 1,2-dibromoethane 2 at room temperature (r.t.) to obtain 9-(2-bromoethyl)-9H-purin-6amine 1 in moderate yield (53 %). A was also treated with 1,3dibromopropane 4 to generate the 9-(3-bromopropyl)-9Hpurin-6-amine 3 in good yield (77 %) (Scheme 1), following a similar synthetic procedure.…”
Section: Functionalization Of Nucleobases Via N-alkylation Reactionmentioning
confidence: 99%
“…Some successful examples of T N-alkylations have been reported in the literature. [27,40,44] Following similar conditions to those reported in the literature, although using different alkylating agents, namely 1,2-dibromoethane 2 and 1,3-dibromopropane 4, different reaction conditions were tested such as the use of phase transfer catalysts (PTC), solvents [water, dichloromethane, anhydrous DMF, dimethyl sulfoxide (DMSO), and tetrahydrofuran (THF)], bases (K 2 CO 3 , NaOH and NaH), as well as distinct heating methods [conventional, microwave (MW) and ohmic heating]. However, in most of the cases no reaction occurred, or the expected N-alkylated T was not obtained.…”
Section: Functionalization Of Nucleobases Via N-alkylation Reactionmentioning
confidence: 99%